Pedagogical Transformation of Biology Teacher Candidates: Integration of Computational Thinking into STEM Learning - Nawawi, Nawawi; Herditiya, Herditiya (STKIP Singkawang, 2024)
This study analyzed the effectiveness of integrating Computational Thinking (CT)-based STEM learning in prospective biology teachers at PGRI Pontianak University, exploring students' perceptions, attitudes, challenges, and opportunities. This integration aims to improve critical thinking, creativity, collaboration, and communication skills to address the challenges of the 21st century. Using Sequential Exploratory Design, data were collected qualitatively through interviews and observations, followed by quantitative descriptive analysis based on student questionnaires. This research involved 100 Biology Education students in the 2023/2024 Academic Year. The results showed that STEM-CT integration effectively improved the thinking skills of prospective Biology teachers with positive student perceptions despite technical challenges.